2010
DOI: 10.1016/b978-0-444-53630-3.00008-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids

Abstract: This chapter provides an overview of neurosteroids, especially their impact on the brain, sex differences and therapeutic potentials. Neurosteroids are synthesized within the brain and rapidly modulate neuronal excitability. They are classified as pregnane neurosteroids such as allopregnanolone and allotetrahydrodeoxycorticosterone, and androstane neurosteroids, such as androstanediol and etiocholanone. Neurosteroids such as allopregnanolone are positive allosteric modulators of GABA-A receptors with powerful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(151 citation statements)
references
References 170 publications
2
148
0
1
Order By: Relevance
“…Under pathological conditions, interneuron-astrocyte reciprocal interactions may also be affected. For example, it has been reported that astrocytes activated by an epileptogenic insult increase their synthetic machinery to produce neurosteroids, potent GABA A receptors modulators [106][107][108], that temporally prevent seizure generation and prolong the latent period in animal models of temporal lobe epilepsy [109].…”
Section: Astrocytes Activated By Non-gabaergic Signals Modulate Gabaementioning
confidence: 99%
“…Under pathological conditions, interneuron-astrocyte reciprocal interactions may also be affected. For example, it has been reported that astrocytes activated by an epileptogenic insult increase their synthetic machinery to produce neurosteroids, potent GABA A receptors modulators [106][107][108], that temporally prevent seizure generation and prolong the latent period in animal models of temporal lobe epilepsy [109].…”
Section: Astrocytes Activated By Non-gabaergic Signals Modulate Gabaementioning
confidence: 99%
“…Задержка созревания префронтальных отделов коры у детей с СДВГ является предпосылкой к формирова-нию импульсивности. В пубертатный период половые гормо-ны взаимодействуют с ГАМК-А и NMDA-рецепторами лим-бической системы и увеличивают эмоциональную неста-бильность и импульсивность [18,19]. Задержка созревания теменной и дорсолатеральной префронтальной коры отчасти обусловливает нарушение функций внимания [19].…”
Section: л е к ц и яunclassified
“…By acting as positive allosteric modulators of GABA-A receptors, allopregnanolone, THDOC and androstanediol augment GABAergic neurotransmission and thereby dampen neuronal excitability. Contrariwise, the sulfated neurosteroids may facilitate central excitation by curtailing GABAergic transmission and augmenting calcium flux through the NMDA (glutamate) receptor [5,6]. By impacting GABAergic and glutamatergic pathways, allopregnanolone and THDOC elicit sedative-hypnotic, anticonvulsant and anxiolytic effects relevant to the pathophysiology of epilepsy (see the section Reproductive Hormones and Epilepsy) and various mood disorders.…”
Section: Sex Steroid-neural Interactionsmentioning
confidence: 99%
“…androstanediol and etiocholanone, metabolites of testosterone) and (c) sulfated neurosteroids (e.g pregnanolone sulfate and dehydroepiandrosterone sulfate). Neuroglial cells (astrocytes, oligodendrocytes) and certain neuronal populations are enriched for key enzymes (5α-reductase, 3α- hydroxysteroid oxidoreductase) which catalyze the interconversion of precursor hormones to neurosteroids [5,6,7]. Neurosteroids rapidly modulate neuronal firing by enhancing or attenuating inhibitory GABA-A receptor-mediated chloride (and other ion) conductance at the neuronal membrane.…”
Section: Sex Steroid-neural Interactionsmentioning
confidence: 99%